The key idea is that, if a vector field is conservative, then it has curl 0. Equivalently, if the curl is not 0, then the field is not conservative. But if we find that the curl is 0, that on its own doesn't mean the field is conservative.
1.
![\mathrm{curl}\vec F=\dfrac{\partial(5x+10y)}{\partial x}-\dfrac{\partial(-6x+5y)}{\partial y}=5-5=0](https://tex.z-dn.net/?f=%5Cmathrm%7Bcurl%7D%5Cvec%20F%3D%5Cdfrac%7B%5Cpartial%285x%2B10y%29%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%28-6x%2B5y%29%7D%7B%5Cpartial%20y%7D%3D5-5%3D0)
We want to find
such that
. This means
![\dfrac{\partial f}{\partial x}=-6x+5y\implies f(x,y)=-3x^2+5xy+g(y)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%3D-6x%2B5y%5Cimplies%20f%28x%2Cy%29%3D-3x%5E2%2B5xy%2Bg%28y%29)
![\dfrac{\partial f}{\partial y}=5x+10y=5x+\dfrac{\mathrm dg}{\mathrm dy}\implies\dfrac{\mathrm dg}{\mathrm dy}=10y\implies g(y)=5y^2+C](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%3D5x%2B10y%3D5x%2B%5Cdfrac%7B%5Cmathrm%20dg%7D%7B%5Cmathrm%20dy%7D%5Cimplies%5Cdfrac%7B%5Cmathrm%20dg%7D%7B%5Cmathrm%20dy%7D%3D10y%5Cimplies%20g%28y%29%3D5y%5E2%2BC)
![\implies\boxed{f(x,y)=-3x^2+5xy+5y^2+C}](https://tex.z-dn.net/?f=%5Cimplies%5Cboxed%7Bf%28x%2Cy%29%3D-3x%5E2%2B5xy%2B5y%5E2%2BC%7D)
so
is conservative.
2.
![\mathrm{curl}\vec F=\left(\dfrac{\partial(-2y)}{\partial z}-\dfrac{\partial(1)}{\partial y}\right)\vec\imath+\left(\dfrac{\partial(-3x)}{\partial z}-\dfrac{\partial(1)}{\partial z}\right)\vec\jmath+\left(\dfrac{\partial(-2y)}{\partial x}-\dfrac{\partial(-3x)}{\partial y}\right)\vec k=\vec0](https://tex.z-dn.net/?f=%5Cmathrm%7Bcurl%7D%5Cvec%20F%3D%5Cleft%28%5Cdfrac%7B%5Cpartial%28-2y%29%7D%7B%5Cpartial%20z%7D-%5Cdfrac%7B%5Cpartial%281%29%7D%7B%5Cpartial%20y%7D%5Cright%29%5Cvec%5Cimath%2B%5Cleft%28%5Cdfrac%7B%5Cpartial%28-3x%29%7D%7B%5Cpartial%20z%7D-%5Cdfrac%7B%5Cpartial%281%29%7D%7B%5Cpartial%20z%7D%5Cright%29%5Cvec%5Cjmath%2B%5Cleft%28%5Cdfrac%7B%5Cpartial%28-2y%29%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%28-3x%29%7D%7B%5Cpartial%20y%7D%5Cright%29%5Cvec%20k%3D%5Cvec0)
Then
![\dfrac{\partial f}{\partial x}=-3x\implies f(x,y,z)=-\dfrac32x^2+g(y,z)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%3D-3x%5Cimplies%20f%28x%2Cy%2Cz%29%3D-%5Cdfrac32x%5E2%2Bg%28y%2Cz%29)
![\dfrac{\partial f}{\partial y}=-2y=\dfrac{\partial g}{\partial y}\implies g(y,z)=-y^2+h(y)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%3D-2y%3D%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20y%7D%5Cimplies%20g%28y%2Cz%29%3D-y%5E2%2Bh%28y%29)
![\dfrac{\partial f}{\partial z}=1=\dfrac{\mathrm dh}{\mathrm dz}\implies h(z)=z+C](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%3D1%3D%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dz%7D%5Cimplies%20h%28z%29%3Dz%2BC)
![\implies\boxed{f(x,y,z)=-\dfrac32x^2-y^2+z+C}](https://tex.z-dn.net/?f=%5Cimplies%5Cboxed%7Bf%28x%2Cy%2Cz%29%3D-%5Cdfrac32x%5E2-y%5E2%2Bz%2BC%7D)
so
is conservative.
3.
![\mathrm{curl}\vec F=\dfrac{\partial(10y-3x\cos y)}{\partial x}-\dfrac{\partial(-\sin y)}{\partial y}=-3\cos y+\cos y=-2\cos y\neq0](https://tex.z-dn.net/?f=%5Cmathrm%7Bcurl%7D%5Cvec%20F%3D%5Cdfrac%7B%5Cpartial%2810y-3x%5Ccos%20y%29%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%28-%5Csin%20y%29%7D%7B%5Cpartial%20y%7D%3D-3%5Ccos%20y%2B%5Ccos%20y%3D-2%5Ccos%20y%5Cneq0)
so
is not conservative.
4.
![\mathrm{curl}\vec F=\left(\dfrac{\partial(5y^2)}{\partial z}-\dfrac{\partial(5z^2)}{\partial y}\right)\vec\imath+\left(\dfrac{\partial(-3x^2)}{\partial z}-\dfrac{\partial(5z^2)}{\partial x}\right)\vec\jmath+\left(\dfrac{\partial(5y^2)}{\partial x}-\dfrac{\partial(-3x^2)}{\partial y}\right)\vec k=\vec0](https://tex.z-dn.net/?f=%5Cmathrm%7Bcurl%7D%5Cvec%20F%3D%5Cleft%28%5Cdfrac%7B%5Cpartial%285y%5E2%29%7D%7B%5Cpartial%20z%7D-%5Cdfrac%7B%5Cpartial%285z%5E2%29%7D%7B%5Cpartial%20y%7D%5Cright%29%5Cvec%5Cimath%2B%5Cleft%28%5Cdfrac%7B%5Cpartial%28-3x%5E2%29%7D%7B%5Cpartial%20z%7D-%5Cdfrac%7B%5Cpartial%285z%5E2%29%7D%7B%5Cpartial%20x%7D%5Cright%29%5Cvec%5Cjmath%2B%5Cleft%28%5Cdfrac%7B%5Cpartial%285y%5E2%29%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%28-3x%5E2%29%7D%7B%5Cpartial%20y%7D%5Cright%29%5Cvec%20k%3D%5Cvec0)
Then
![\dfrac{\partial f}{\partial x}=-3x^2\implies f(x,y,z)=-x^3+g(y,z)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%3D-3x%5E2%5Cimplies%20f%28x%2Cy%2Cz%29%3D-x%5E3%2Bg%28y%2Cz%29)
![\dfrac{\partial f}{\partial y}=5y^2=\dfrac{\partial g}{\partial y}\implies g(y,z)=\dfrac53y^3+h(z)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%3D5y%5E2%3D%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20y%7D%5Cimplies%20g%28y%2Cz%29%3D%5Cdfrac53y%5E3%2Bh%28z%29)
![\dfrac{\partial f}{\partial z}=5z^2=\dfrac{\mathrm dh}{\mathrm dz}\implies h(z)=\dfrac53z^3+C](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%3D5z%5E2%3D%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dz%7D%5Cimplies%20h%28z%29%3D%5Cdfrac53z%5E3%2BC)
![\implies\boxed{f(x,y,z)=-x^3+\dfrac53y^3+\dfrac53z^3+C}](https://tex.z-dn.net/?f=%5Cimplies%5Cboxed%7Bf%28x%2Cy%2Cz%29%3D-x%5E3%2B%5Cdfrac53y%5E3%2B%5Cdfrac53z%5E3%2BC%7D)
so
is conservative.
Answer:
2x-5
remainder of 0
Step-by-step explanation:
Check the image
Answer:
the values of x, y and z are x= 2, y =-1 and z=1
Step-by-step explanation:
We need to solve the following system of equations.
We will use elimination method to solve these equations and find the values of x, y and z.
2x + 2y + 5z = 7 eq(1)
6x + 8y + 5z = 9 eq(2)
2x + 3y + 5z = 6 eq(3)
Subtracting eq(1) and eq(3)
2x + 2y + 5z = 7
2x + 3y + 5z = 6
- - - -
_____________
0 -y + 0 = 1
-y = 1
=> y = -1
Subtracting eq(2) and eq(3)
6x + 8y + 5z = 9
2x + 3y + 5z = 6
- - - -
______________
4x + 5y +0z = 3
4x + 5y = 3 eq(4)
Putting value of y = -1 in equation 4
4x + 5y = 3
4x + 5(-1) = 3
4x -5 = 3
4x = 3+5
4x = 8
x= 8/4
x = 2
Putting value of x=2 and y=-1 in eq(1)
2x + 2y + 5z = 7
2(2) + 2(-1) + 5z = 7
4 -2 + 5z = 7
2 + 5z = 7
5z = 7 -2
5z = 5
z = 5/5
z = 1
So, the values of x, y and z are x= 2, y =-1 and z=1
Set it up with variables; tomatoes=t, sunflowers=s, corn=c
320=t+s+c
This year;
t=2s
c=t+40
so, replace 2s for t; c=2s+40
now we can put those factors in for 320=t+c+s
320= 2s+2s+40+s
(SIMPLIFY)---> 320=5s+40----> 5s+280----> s=56
now incorporate the s value into the other equations.
c=2s+40----> c=56(2)=40 ----> c=152
t=2s -----> t=2(56) ----> t=112
TOMATOES= 112 acres
CORN= 152 acres
SUNFLOWERS= 56 acres
To check your work: 320=t+s+c ----> 320=112+156+56
The difference between the two mass is 151950g
Data;
- Mass a = 29.48kg
- Mass b = 181,430g
<h3>Difference Between The Mass</h3>
To calculate the difference between the mass, we must do so in the same unit. i.e both mass a and mass b must be in the same unit.
<h3>Conversion of Mass from Kg to g</h3>
Let's convert mass a from kg to g
![1kg = 1000g](https://tex.z-dn.net/?f=1kg%20%3D%201000g)
Using this, we can find how many grammes are in 29.48kg
![1kg = 1000g\\29.48kg = x\\x = 29.48 * 1000\\x = 29480g](https://tex.z-dn.net/?f=1kg%20%3D%201000g%5C%5C29.48kg%20%3D%20x%5C%5Cx%20%3D%2029.48%20%2A%201000%5C%5Cx%20%3D%2029480g)
Now we can find the difference between mass b and mass a
![b - a = 181430 - 29480 = 151950](https://tex.z-dn.net/?f=b%20-%20a%20%3D%20181430%20-%2029480%20%3D%20151950)
The difference between the two mass is 151950g
Learn more on difference between two numbers here;
brainly.com/question/18591813